2019
DOI: 10.1038/s41431-018-0295-z
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association meta-analysis of 30,000 samples identifies seven novel loci for quantitative ECG traits

Abstract: Genome-wide association studies (GWAS) of quantitative electrocardiographic (ECG) traits in large consortia have identified more than 130 loci associated with QT interval, QRS duration, PR interval, and heart rate (RR interval). In the current study, we meta-analyzed genome-wide association results from 30,000 mostly Dutch samples on four ECG traits: PR interval, QRS duration, QT interval, and RR interval. SNP genotype data was imputed using the Genome of the Netherlands reference panel encompassing 19 million… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 50 publications
2
36
0
Order By: Relevance
“…To summarise, in meta-analyses of nearly 300,000 individuals we identified 210 loci, of which 149 were novel, underlying cardiac conduction as manifested by the electrocardiographic PR interval. Apart from confirming well-established associations in loci harbouring ion-channel genes, our findings further underscore the central importance of heart development and cytoskeletal components in atrioventricular conduction 10,12,13 . We also highlight the role of common variation at loci harboring genes underlying monogenic forms of heart disease in cardiac conduction.…”
Section: Main Textsupporting
confidence: 79%
“…To summarise, in meta-analyses of nearly 300,000 individuals we identified 210 loci, of which 149 were novel, underlying cardiac conduction as manifested by the electrocardiographic PR interval. Apart from confirming well-established associations in loci harbouring ion-channel genes, our findings further underscore the central importance of heart development and cytoskeletal components in atrioventricular conduction 10,12,13 . We also highlight the role of common variation at loci harboring genes underlying monogenic forms of heart disease in cardiac conduction.…”
Section: Main Textsupporting
confidence: 79%
“…The PR interval also serves as a risk factor for atrial fibrillation and cardiovascular mortality [1][2][3] . Prior genetic association studies have identified 64 PR interval loci [4][5][6][7][8][9][10][11][12][13] . Yet the underlying biological mechanisms of atrioventricular conduction and relationships between genetic predisposition to PR interval duration and disease are incompletely characterized.…”
mentioning
confidence: 99%
“…Given that the minor allele was associated with a worse outcome in both discovery and validation cohorts, one could postulate that an increased expression of SGIP1 and a decreased expression of TCTEX1D1 could be deleterious for the cardiac phenotype in patients with DMD. Interestingly, a recent GWA meta-analysis for quantitative electrocardiography traits, showed that variants in the TCTEX1D1/SGIP1 locus are associated with QT interval [45]. More research (e.g.…”
Section: Discussionmentioning
confidence: 99%